Role of Preoperative Intravenous Steroid Injection in Preventing Seroma Formation After Breast Surgeries - Bashir, Shaza; Hussain, Syed Mukarram; Khan, Waseem Ahmad; Ahmad, Muhammad; Maqbool, Adil; Anwar, Fawad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the role of preoperative intravenous steroid injection in preventing seroma formation after breast surgeries. Study Design: Quasi-experimental study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Jul to Dec 2023. Methodology: With non-probability consecutive sampling technique, a total of 40 patients were included who were scheduled for breast surgeries. 20 patients were grouped into Group-I who were not given steroid before surgery. Group-II also consisted of 20 patients who were injected 120 mg intravenous injection of methylprednisolone one hour prior to surgery. Post-surgery the amount of drainage and number of drainage days were recorded in milliliters. At each follow up visit, wound was also examined for any infection or necrosis. Results: Patients ranged in age from 18 to 69 years, with a mean age of 56.83+6.91. Methylprednisolone injection given to the patients of Group-II helped reduce the average drain output and number of days for which drainage was required and was statistically significant. 25% of patients reported with seroma formation in Group-II and only 5% of which underwent surgical/ IR guided intervention as compared to 45% in Group-I with 15% undergoing surgical/ IR guided intervention. Conclusion: A single dose of intravenous steroid injection (methylprednisolone) given an hour before surgery is a promising and effective strategy to prevent seroma formation following breast surgical procedures without any significant complications or side effects.